2022
DOI: 10.1016/j.trip.2022.100540
|View full text |Cite
|
Sign up to set email alerts
|

Transport impacts in Germany and State of Qatar: An assessment during the first wave of COVID-19

Abstract: Response measures to contain COVID-19 spread varied from country to country, some imposed a complete lockdown while some imposed partial restrictions. This paper compares the transport impacts of the COVID-19 pandemic for two countries having dissimilar characteristics, Germany and State of Qatar, based on the rates of infection and response measures. Secondary data, obtained from Google mobility reports, and primary data, collected from local agencies, were used for comparison purposes. The secondary data com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…They often reacted violently to rule-breaking or inappropriate behaviour by others who refused to wear a facemask or keep an expected distance, which often led to strong feelings of discomfort, annoyance or even fear. Our study complements previous research showing not only that “fear has a significant impact on travel behaviour” ( Kim, et al 2017 , 2894) and that risk perception varies by socio-demographic characteristics ( Jaekel & Muley, 2022 ), but that fear is above all unequally distributed (see Figure 1 ). Comparing the changes experienced in PT compared to other urban public spaces, such as markets and parks, the survey shows that a certain type of respondent perceives PT as relatively safe, that is, passengers who continue to use PT consider it to be about as safe or even safer than other shared spaces such as grocery shops or shopping centres ( Figure 6 ).…”
Section: A Narrative Of Fear and Its Unequal Distributionsupporting
confidence: 89%
See 1 more Smart Citation
“…They often reacted violently to rule-breaking or inappropriate behaviour by others who refused to wear a facemask or keep an expected distance, which often led to strong feelings of discomfort, annoyance or even fear. Our study complements previous research showing not only that “fear has a significant impact on travel behaviour” ( Kim, et al 2017 , 2894) and that risk perception varies by socio-demographic characteristics ( Jaekel & Muley, 2022 ), but that fear is above all unequally distributed (see Figure 1 ). Comparing the changes experienced in PT compared to other urban public spaces, such as markets and parks, the survey shows that a certain type of respondent perceives PT as relatively safe, that is, passengers who continue to use PT consider it to be about as safe or even safer than other shared spaces such as grocery shops or shopping centres ( Figure 6 ).…”
Section: A Narrative Of Fear and Its Unequal Distributionsupporting
confidence: 89%
“…Affecting urban lives and travel worldwide, the COVID-19 outbreak brought about a surge of research on how the pandemic relates to issues of mobility, whether in everyday life, for leisure or tourism travels. Besides a general observation that ridership dropped by up to 60% in some European cities, studies focusing on the first months of the pandemic found that the decline in PT ridership reflected a lower number of active users and was accompanied by a shift to other modes of transport such as car, bicycle or walking ( Bucsky, 2020 , Jaekel and Muley, 2022 , Jenelius and Cebecauer, 2020 , Molloy et al, 2020 ). Further literature concentrates on PT as a space of increased risk of contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies outside China showed similar patterns (Jaekel and Muley 2022;Cintia et al 2020). Mobility patterns derived from mobile phone data in 25 US counties showed a strong correlation, with Pearson correlation coefficients above 0.7 for 20 of the 25 counties (Badr et al 2020;Kissler et al 2020) observed that the mean estimated prevalence of COVID-19 infection by borough in New York City was strongly negatively correlated with reduced commuting (-0.88Iacus et al (2020b) also confirmed that human mobility (internal and outbound movements) had a high impact on initial virus spread in case studies of France, Italy, and Spain, with between 52% and 92% in France, up to 91% in Italy, and up to 75% in Spain.…”
Section: Relationship Between Human Mobility and Covid-19 Transmissionmentioning
confidence: 77%
“…Given the pandemic's severity, it is a crucial that governments control the spread. Therefore, they implemented a combination of measures, applying various approaches to isolate outbreaks and avoid further exposures by reducing close contact with the virus (Jaekel and Muley 2022;Wang et al 2022;Arimura et al 2020;Lau et al 2020). These countermeasures included forced or recommended measures, such as city lockdowns, confinement, halting domestic and international flights, travel restrictions, workplace closures, and social distancing (Chen et al 2022a;Lu et al 2021;Pan et al 2020;Chinazzi et al 2020;Shakibaei et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) that started at the beginning of the year 2020 has significantly disrupted people's daily life and forced governments worldwide to rapidly enact several restrictions to face the associated health emergency (Wilder-Smith, 2020). The German government, likewise (Jaekel, 2022), established various limitations to flatten the contagions curve. The impact on Urban mobility was evident, but it took a while to identify suitable approaches and strategies to mitigate the spread of the virus, protect the population and maintain a balanced urban mobility system.…”
Section: Introductionmentioning
confidence: 99%